SOME CHARACTERISTICS OF TERMITARIA SOIL OF MACROTERMES ESTHERAE (DESNEUX) AND TRINERVITERMES BIFORMIS (WASMANN) IN RELATION TO THEIR SURROUNDINGS IN KERALA - MIRANDA, M.T.P.; D'CRUZ, F.G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
Physical characteristics such as mechanical composition, water holding capacity and chemical parameters like pH, organic matter, total nitrogen, calcium, magnesium, sodium, potassium, iron and phosphorus content of termite soil and surrounding soil was analyzed for Macrotermes estherae and Trinervitermes biformis-two widely distributed subterranean termites found in Kerala. The nest soil of both the species recorded a higher water holding capacity. Gravel was totally absent in termitaria soil. There was no significant variation in the proportion of coarse sand, fine sand and clay fractions between the nest soil and surrounding soil of M. estherae where as the gallery soil of T. biformis contained significantly higher proportions of coarse sand, fine sand, silt and clay than the adjacent soil. Most of the chemical parameters tested recorded significantly higher proportions in the termitaria soil of both species. The study indicates that temitaria soil can be used as a cheap and eco-friendly fertilizer.